2015
DOI: 10.1371/journal.pone.0117508
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HmuY Antibodies Specifically Recognize Porphyromonas gingivalis HmuY Protein but Not Homologous Proteins in Other Periodontopathogens

Abstract: Given the emerging evidence of an association between periodontal infections and systemic conditions, the search for specific methods to detect the presence of P. gingivalis, a principal etiologic agent in chronic periodontitis, is of high importance. The aim of this study was to characterize antibodies raised against purified P. gingivalis HmuY protein and selected epitopes of the HmuY molecule. Since other periodontopathogens produce homologs of HmuY, we also aimed to characterize responses of antibodies rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 54 publications
0
35
0
4
Order By: Relevance
“…Mutant strains were maintained in the presence of 1 µg/mL erythromycin and complemented mutant strains in the presence of 1 µg/mL of tetracycline and 1 µg/mL erythromycin. Prevotella intermedia strain 17 (GenBank: CP003502.1 and CP003503.1) and Tannerella forsythia (ATCC 43037) were maintained as described previously [37]. Streptococcus gordonii (ATCC 10558) was grown in TSB agar or liquid medium (5% TBS) under an increased concentration of CO 2 using the Atmosphere generation system (Thermo Scientific, Waltham, MA, USA) as reported previously [16].…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…Mutant strains were maintained in the presence of 1 µg/mL erythromycin and complemented mutant strains in the presence of 1 µg/mL of tetracycline and 1 µg/mL erythromycin. Prevotella intermedia strain 17 (GenBank: CP003502.1 and CP003503.1) and Tannerella forsythia (ATCC 43037) were maintained as described previously [37]. Streptococcus gordonii (ATCC 10558) was grown in TSB agar or liquid medium (5% TBS) under an increased concentration of CO 2 using the Atmosphere generation system (Thermo Scientific, Waltham, MA, USA) as reported previously [16].…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…A lipoproteína HmuY é específica de P. gingivalis e anticorpos anti-HmuY não reconhecem proteínas homólogas em outros periodontopatógenos (OLCZAK et al, 2010;ŚMIGA et al, 2015). HmuY apresenta-se associada à membrana externa de P.…”
Section: A Lipoproteína Hmuyunclassified
“…Indeed, we found that anti-HmuY antibodies inhibited P. gingivalis growth and biofilm formation [ 91 ]. Antibodies directed against P. gingivalis A7436 and ATCC 33277 HmuY are highly specific for the purified HmuY protein and cell-bound HmuY and do not cross-react with HmuY homologs found in P. intermedia and T. forsythia [ 102 ]. This suggests that P. gingivalis ATCC 33277, W83, and A7436 HmuY can serve as a specific antigen for serum determination of antibodies raised against this bacterium in patients with chronic periodontitis [ 103 ].…”
Section: Antigenic Determinants Of Porphyromonas Gingivamentioning
confidence: 99%